1998
DOI: 10.1007/s11661-998-0025-1
|View full text |Cite
|
Sign up to set email alerts
|

Intergranular fracture of gamma titanium aluminides under hot working conditions

Abstract: A comparative study of the hot workability of a near gamma titanium aluminide alloy Ti-49.5Al-2.5Nb-1.1Mn in the cast and wrought conditions was performed. Tension tests conducted on coarse grain, cast material, and fine grain wrought material revealed a pronounced variation in both fracture/peak stress and ductility with temperature and strain rate. Brittle, intergranular fracture occurring at high strain rates was found to be controlled by wedge crack nucleation, whereas the ductile fracture observed at low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…11a). It is observed that such cracks are found to be associated with coarse γ-grain present at the colony boundaries in accordance with reported studies [31]. It is interesting to note the high strain gradient associated with such coarse γ-grain ( Fig.…”
Section: Wedge and Cavitation Damagesupporting
confidence: 91%
See 3 more Smart Citations
“…11a). It is observed that such cracks are found to be associated with coarse γ-grain present at the colony boundaries in accordance with reported studies [31]. It is interesting to note the high strain gradient associated with such coarse γ-grain ( Fig.…”
Section: Wedge and Cavitation Damagesupporting
confidence: 91%
“…7c-inset). It has been proposed that grain boundary sliding plays a major role in the nucleation of both wedge cracks and cavities [29][30][31]. Due to the lack of adequate matrix slip and grain boundary diffusion in γ-TiAl alloys, especially at low temperature and high strain rates, grain boundary sliding leads to stress concentration at the colony boundaries and triple junctions.…”
Section: Wedge and Cavitation Damagementioning
confidence: 99%
See 2 more Smart Citations
“…Figure 12 shows the relationship between the peak stress and T. The activation energy of the hot deformation Q p is determined to be about 319 kJ mol 21 . A plot of ln[sinh(as)]-lnZ is show in Fig.…”
Section: Discussionmentioning
confidence: 99%